Parameter Based Efficient & Reliable Routing Technique to Enhance Network Lifetime for Vehicular Ad Hoc Networks - K S, Asha; Hegde, Rajeshwari (International Journal of Engineering and Technology, 2018)
Some Inherent Vehicular Ad Hoc Networks (VANETs) characteristics such as intermittent connectivity, highly dynamic topology, and hard delay constraints, make data communication a challenging task in these networks. Due to such peculiarities, in this paper we study the impact of using vehicles predicted locations as a metric for data communication in VANETs. This paper deals with PBERR (Parameter Based Efficient Reliable Routing) for VANETs, which is a multilevel routing algorithm. The focus of this algorithm is 100% data transmission from end to end with no loss or drop of data packets by selecting the reliable path. The proposed algorithm will use the data of the digital maps to limit the scope of message exchanges in the shortest path for vehicles between source and destination. Our results clearly demonstrate the efï¬ciency of the proposed solution in different scenarios, especially in terms of Network throughput, Energy consumption and Average delay.Â